Does Investor Attention Affect Stock Trading and Returns? Evidence from Publicly Listed Firms in China. Issue 4 (18th October 2021) - Yang, Dan; Ma, Tingyu; Wang, Yuetang; Wang, Guojun
Abstract: Limited attention is an inevitable outcome of voluminous information. Investors facing a large number of stocks can only focus on a few and endeavor to have access to in-depth knowledge. Since the retrieved knowledge would affect investors' decisions, investor attention becomes a factor in affecting stock returns and trading volumes. Through using 890, 840 firm-week observations of Chinese listed firms between 2011 and 2018 as a sample, we document that investor attention, measured by abnormal Baidu search volume index (ASVI), is positively associated with contemporaneous stock returns but with a complete reversal in the subsequent period; and ASVI exhibits a positive link with trading volumes without a subsequent reversal, but its predictable ability becomes weaker in subsequent weeks. The effect of ASVI is pronounced for the ChiNext market and firms with higher level of financial transparency. We further find investor attention has been driven by five corporate events including earnings announcements, management forecasts, financial analysts following, mergers and acquisitions and dividend payout. This paper contributes to the theory of limited attention through using a direct measure of attention, providing evidence on its economic consequences in the Chinese stock market and exploring specific events that drive investor attention.